The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2019
DOI: 10.1128/jvi.02128-18
|View full text |Cite
|
Sign up to set email alerts
|

The Polar Region of the HIV-1 Envelope Protein Determines Viral Fusion and Infectivity by Stabilizing the gp120-gp41 Association

Abstract: HIV-1 enters cells through binding between viral envelope glycoprotein (Env) and cellular receptors to initiate virus and cell fusion. HIV-1 Env precursor (gp160) is cleaved into two units noncovalently bound to form a trimer on virions, including a surface unit (gp120) and a transmembrane unit (gp41) responsible for virus binding and membrane fusion, respectively. The polar region (PR) at the N terminus of gp41 comprises 17 residues, including 7 polar amino acids. Previous studies suggested that the PR contri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(30 citation statements)
references
References 41 publications
1
29
0
Order By: Relevance
“…We expect that the changes in the FPPR induce similar release of structural constraints that maintain the trimer in a closed conformation. Based on proximity of the FPPR to the CHR, is it likely that the FPPR substitutions affect the interaction between the two domains (28). The nature of the association between the MPER and other components of gp41, which can explain the structural basis for our observations, remains to be clarified.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…We expect that the changes in the FPPR induce similar release of structural constraints that maintain the trimer in a closed conformation. Based on proximity of the FPPR to the CHR, is it likely that the FPPR substitutions affect the interaction between the two domains (28). The nature of the association between the MPER and other components of gp41, which can explain the structural basis for our observations, remains to be clarified.…”
Section: Discussionmentioning
confidence: 91%
“…In the unliganded form of Env (i.e., not bound to CD4), the FPPR appears to be conformationally flexible (25,26). Nevertheless, substitutions at some FPPR positions increase detachment of gp120 from virions (27,28), supporting the notion that this region contributes to structural stability of the trimer. We analyzed the historical changes in amino acid sequence of the FPPR among clade B viruses and tested the emerging variants for their fitness and antigenicity.…”
Section: Introductionmentioning
confidence: 80%
“…Specifically, the N36/C34 complex showed 89% α-helices with a melting temperature ( T m ) value of 63 ℃, whereas the N36/C34 N145A complex showed 81% α-helices with a T m of 51 ℃. Because the recent studies suggested that the interactions between the FPPR of NHR and the TRM of CHR also critically determine the NHR-CHR interactions and HIV-1 entry [14,22,34], we further used the NHR-derived peptide N39, the inhibitor T20, and its N145A mutant as surrogates. As shown in Figure 4C-D, the N39/T20 complex displayed 53% α-helices with a T m of 43 ℃, but the α-helical content and T m of the N39/T-20 N145A complex could not be defined, which suggested that the N145A substitution disrupted the helical interaction between N39 and T20.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies suggested that the PR participates in Env peptide-based membrane fusion ( 5 9 ); however, the function of the PR is not fully understood. We have reported that the PR is highly conserved and determines viral fusion and infectivity ( 10 ). We characterized three PR mutants ( 10 ) containing S534P/T536A, S534P/T536A/T538A or S534P, named M1, M3 or M4, respectively ( Fig.…”
mentioning
confidence: 99%
“…We have reported that the PR is highly conserved and determines viral fusion and infectivity ( 10 ). We characterized three PR mutants ( 10 ) containing S534P/T536A, S534P/T536A/T538A or S534P, named M1, M3 or M4, respectively ( Fig. 1A ).…”
mentioning
confidence: 99%